Porous bioceramic composition for bone repair - Abu Bakar @ Zakaria, Md Zuki; Hussein, Bahaa Fakri; Mohamed Mustapha, Noordin; Yusof, Norimah; Saion, Elias (2009)
The Present invention relates to a porous bioceramic composition for bone repair and method of fabrication of the same. 3D-scaffolds were fabricated with a novel micro- and macro-architecture. Porous scaffolds based on dextrin, dextran, gelatin and biomineral (CaCO3) powder were fabricated by heating and freeze-drying methods. Fabrication of different compositions of porous scaffolds (gelatin, dextrin,dextran bounder with the constant quantity of CaCO3). The scaffolds properties were characterised by x-ray diffraction (XRD), differential scanning calorimetry (DSC), scanning electron microscopy (SEM) and compression tests.